Cyclooxygenase inhibition attenuates brain angiogenesis and independently decreases mouse survival under hypoxia. Issue 2 (25th February 2021) - Seeger, Drew R.; Golovko, Svetlana A.; Grove, Bryon D.; Golovko, Mikhail Y.
Abstract: Although cyclooxygenase (COX) role in cancer angiogenesis has been studied, little is known about its role in brain angioplasticity. In the present study, we chronically infused mice with ketorolac, a non‐specific COX inhibitor that does not cross the blood–brain barrier (BBB), under normoxia or 50% isobaric hypoxia (10% O2 by volume). Ketorolac increased mortality rate under hypoxia in a dose‐dependent manner. Using in vivo multiphoton microscopy, we demonstrated that chronic COX inhibition completely attenuated brain angiogenic response to hypoxia. Alterations in a number of angiogenic factors that were reported to be COX‐dependent in other models were assayed at 24‐hr and 10‐day hypoxia. Intriguingly, hypoxia‐inducible factor 1 was unaffected under COX inhibition, and vascular endothelial growth factor receptor type 2 (VEGFR2) and C‐X‐C chemokine receptor type 4 (CXCR4) were significantly but slightly decreased. However, a number of mitogen‐activated protein kinases (MAPKs) were significantly reduced upon COX inhibition. We conclude that additional, angiogenic factor‐independent mechanism might contribute to COX role in brain angioplasticity, probably including mitogenic COX effect on endothelium. Our data indicate that COX activity is critical for systemic adaptation to chronic hypoxia, and BBB COX is essential for hypoxia‐induced brain angioplasticity. These data also indicate a potential risk for using COX inhibitors under hypoxia conditions in clinics. Further studies are required to elucidate a complete mechanism for brain long‐term angiogenesis regulation through COX activity. Abstract : The role of cyclooxygenase (COX) in cancer angiogenesis has been extensively studied but its role in brain angioplasticity is unknown. Under brain hypoxia, partial pharmacological inhibition of COX decreased mitogen‐activated protein kinases (MAPK) and arrested angiogenesis with only limited alterations in angiogenic factors and corresponding receptors, that is, vascular endothelial growth factor/receptors, fibroblast growth factors/receptors, angiopoietins/receptors, C‐X‐C chemokine receptor, and hypoxia‐inducible factors. A complete COX inhibition decreased survival under hypoxia. We conclude that activation of COX and downstream prostaglandin formation are required for hypoxia‐induced brain angiogenesis through MAPK‐mediated mitogenic effect downstream of angiogenic factors, as well as survival under hypoxia